1998
DOI: 10.1152/ajplung.1998.275.6.l1184
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternal vitamin A status on fetal heart and lung: changes in expression of key developmental genes

Abstract: Vitamin A is required during pregnancy for fetal lung development. These experiments monitored fetal lung morphology in normal and vitamin A-deficient rats. The expression of elastin and the growth arrest-specific gene 6 ( gas6) in fetal and neonatal hearts and lungs was assessed by Northern blotting. In normal-fed rats, elastin and gas6 were expressed in the fetal lung and heart from day 19 of gestation up to day 2 postnatally. Maternal vitamin A deficiency altered fetal lung development. On day 20, the bronc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 17 publications
2
29
1
1
Order By: Relevance
“…Rat embryos which are deprived at later stages have an underdeveloped hindbrain, loss of posterior cranial nerves and posterior branchial arches, microphthalmia, narrow limb buds, neural crest cell death, failure or hypoplasia of lung development, failure of septation of the trachea and oesophagus, and lack of differentiation of neuronal populations in the brain (Dickman et al 1997;Antipatis et al 1998;White et al 1998). These studies have confirmed the role that RA plays in many systems of the embryo and at many times throughout development rather than at any one stage of development.…”
Section: Deprivation Studiesmentioning
confidence: 99%
“…Rat embryos which are deprived at later stages have an underdeveloped hindbrain, loss of posterior cranial nerves and posterior branchial arches, microphthalmia, narrow limb buds, neural crest cell death, failure or hypoplasia of lung development, failure of septation of the trachea and oesophagus, and lack of differentiation of neuronal populations in the brain (Dickman et al 1997;Antipatis et al 1998;White et al 1998). These studies have confirmed the role that RA plays in many systems of the embryo and at many times throughout development rather than at any one stage of development.…”
Section: Deprivation Studiesmentioning
confidence: 99%
“…Several studies have shown the importance of vitamin A for proper lung morphogenesis and respiratory epithelium differentiation [Wilson et al, 1953;Antipatis et al, 1998;Morriss-Kay and Ward, 1999;Barlier-Mur et al, 2003;Perrotta et al, 2003]. Vitamin A deficiency was found to perturb lung branching morphogenesis and to alter the expression of pattern-related genes [Chailley-Heu et al, 1999].…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that maternal MVAD decreased body weight and lung weight of the newborn, but body weight showed no difference compared to the control at 8 wk of age. Other researches also have established that maternal VAD in the rat has marked effects on the fetus and neonate including impaired fetal lung development (13,14,32). It indicated that MVAD affects fetal and early postnatal lung viability, and can last to adulthood.…”
Section: Mvad From Prenatal Stage Reduces Body Weight and Lung Weightmentioning
confidence: 99%